Long and short branched chain type perfluorinated sulfonic acid resin, proton membrane and preparation method and application of long and short branched chain type perfluorinated sulfonic acid resin
The long-short branch type perfluorosulfonic acid resin addresses the swelling and conductivity issues in PFSA membranes by incorporating specific structural units, resulting in enhanced mechanical stability and ionic conductivity, and improved ion blocking properties for better fuel cell performance.
Patent Information
- Application Number
- CN202311283535.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
Traditional PFSA membranes suffer from excessive swelling due to high water absorption, leading to mechanical weakness, ion selectivity issues, and reduced energy efficiency in applications like fuel cells, which existing methods like PTFE composite membranes attempt to address but with limited success due to compatibility issues and loss of ionic conductivity.
A long-short branch type perfluorosulfonic acid resin with a specific structural composition that includes perfluoroethylene units, short and long branch perfluorosulfonic acid units, and ion exchange groups, allowing for controlled ion exchange capacity and improved mechanical stability while maintaining high ionic conductivity.
The solution effectively enhances the mechanical stability and ionic conductivity of the membrane, resolving the trade-off between swelling and conductivity, and exhibits superior blocking properties for ions like vanadium, thus improving the membrane's performance in fuel cells.
Smart Images

Figure CN119708298A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials and relates to a long- and short-chain branched perfluorosulfonic acid resin, a proton membrane and a preparation method and application thereof. Background Art
[0002] The traditional homogeneous perfluorosulfonic acid proton exchange membrane (PFSA) is prepared by an ion exchange resin with a single cation exchange function. Its main chain structure is a strongly hydrophobic polytetrafluoroethylene (Teflon) skeleton, and the side chain has a single hydrophilic cation exchange group (-SO3 - , negatively charged groups) side chains. The hydrophilic cationic groups on the side chains of perfluorosulfonic acid resins will undergo a hydrophilic / dispersive microphase separation with the hydrophobic main chain structure, thereby forming nanoscale sulfonic acid ion clusters that are evenly distributed in the continuous CF lattice (polymer crystal region). Under working conditions, the transfer of ions in PFSA is conducted by the sulfonic acid groups reacting with water to form hydrated protons. The high water absorption rate of a single sulfonic acid group causes an expansion-de-expansion process in the PFSA proton membrane, which causes serious swelling problems, causing the membrane to deform and even cause problems such as pinholes or cracks, significantly reducing the mechanical strength of the membrane. In addition, severe swelling problems lead to a reduction in the ion selectivity of the ion exchange membrane, such as the permeation of hydrogen in fuel cells, the permeation of methanol, and the permeation of vanadium ions in vanadium batteries, which leads to a reduction in the selectivity of cations, thereby reducing the energy efficiency of the battery.
[0003] In view of the above-mentioned problems existing in the current PFSA membrane, the currently used method includes using polytetrafluoroethylene membrane (PTFE) and PFSA to compound to improve the tensile strength of the proton exchange membrane and reduce swelling, and this method has achieved certain results. For example, CN101692487A uses a method of combining ultrasonic impregnation and spraying to compound PFSA resin on the surface of an expanded PTFE microporous film, wherein the ultrasonic impregnation is to immerse the expanded PTFE microporous film in a PFSA solution with the assistance of ultrasonic means; and the spraying is to repeatedly cover and spray the expanded PTFE membrane after ultrasonic impregnation to prepare a proton exchange membrane of a predetermined thickness. CN101667648A discloses a method for PTFE composite membrane, in which the perfluorosulfonic acid resin component and the silicon dioxide component are filled into the micropores of the expanded polytetrafluoroethylene microporous film by impregnation, and the thickness of the composite proton exchange is controlled by spraying the perfluorosulfonic acid resin component and the silicon dioxide component. However, due to the poor compatibility between hydrophobic PTFE and hydrophilic PFSA, surface treatment must be done in advance, and the composite process is relatively complicated. In addition, PTFE itself does not have proton conduction function, and the resulting composite membrane will inevitably lose its ion conduction performance and face the problem of low conductivity.
[0004] Research has found that by extending the length of the side chain molecular chain, the water absorption rate of PFSA can also be reduced, effectively limiting the excessive swelling of the membrane. However, blindly extending the molecular chain length will lose the ion exchange capacity of PFSA, leading to problems such as low membrane ion conductivity and attenuated mass transfer performance. In addition, shortening the length of the side chain molecular chain can increase the conductivity of PFSA. However, shortening the length of the side chain molecular chain will increase the ion exchange capacity of PFSA, leading to problems such as excessive water absorption and high swelling of the membrane. How to maintain high conductivity while ensuring the stability of the membrane material is still a great challenge. Summary of the invention
[0005] In order to solve the excessive swelling problem of perfluorosulfonic acid proton exchange membrane (PFSA), the present invention provides a long and short branched perfluorosulfonic acid resin, a proton membrane and a preparation method and application thereof from the perspective of resin structure.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The long and short branched perfluorosulfonic acid resin is characterized in that the resin structure includes a perfluoroethylene structural unit, a short branched perfluorosulfonic acid structural unit (A) and a long branched perfluorosulfonic acid structural unit (B), and the resin has a structure shown in the following formula I:
[0008]
[0009] wherein ad is an integer of 0 to 30, x is 0 or 1; y, z are integers of 0 to 3, preferably a, c are 1 to 10; b, d = 1; x = 1; y, z = 0, 1; e is the number of repeating units, and e is 50 to 10000; a+b / (a+b+c+d) = 0.30 to 0.90; c+d / (a+b+c+d) = 0.40 to 0.80; preferably a+b / (a+b+c+d) = 0.45 to 0.70; c+d / (a+b+c+d) = 0.30 to 0.55; further preferably a+b / (a+b+c+d) = 0.50 to 0.65; c+d / (a+b+c+d) = 0.35 to 0.50;
[0010] In the structural unit B, m is an integer ≥2, and preferably m is an integer of 2-6.
[0011] Ar in the structural unit B is a cationic group.
[0012] Preferably, the cationic group is H + Or it is composed of a cationic structure and a counter ion containing one of the structures in Formula II:
[0013]
[0014] The counter ions are Cl-, SO4 2- , HSO4 - , one of the OH-.
[0015] Further preferably, the Ar is H+ or One of them.
[0016] Preferably, the molar percentages of the polymer units in the resin are as follows: the molar percentage of tetrafluoroethylene structural units is 35-85%, the molar percentage of short-chain branched perfluorosulfonic acid structural units is 10-60%, and the molar percentage of long-chain branched perfluorosulfonic acid structural units is 5-55%.
[0017] Further preferably, the molar percentage of each polymer unit in the resin is: the molar percentage of tetrafluoroethylene structural unit is 40-60%, the molar percentage of short-chain branched perfluorosulfonic acid structural unit is 20-35%, and the molar percentage of long-chain branched perfluorosulfonic acid structural unit is 20-35%.
[0018] More preferably, the molar proportion of tetrafluoroethylene structural units is 45-49%, the molar proportion of short-chain branched perfluorosulfonic acid structural units is 21-28%, and the molar proportion of long-chain branched perfluorosulfonic acid structural units is 23-30%.
[0019] The resin has both cation exchange capacity and anion exchange capacity, and the ion exchange capacity is 0.9 to 2.0 mmol / g, more preferably 1.0 to 1.5 mmol / g.
[0020] The present invention also provides a method for preparing the long and short branched perfluorosulfonic acid resin, comprising the following steps:
[0021] Step 1: After PFSO2F is pre-swollen in an organic solvent, it is reacted with an ammonia reagent to convert part of the -SO2F groups into -SO2NH2, and then the remaining -SO2F groups are converted into sulfonate -SO3M (M is K) through an alkaline ion exchange process. + , Na + ), after washing and drying, a long and short branched chain intermediate product is obtained, and the reaction formula is as follows:
[0022]
[0023] Step 2:
[0024] Method (1), when Ar is H + When the intermediate product is directly reacted with Q-Ar2 reagent to graft long-chain -SO3 - , forming -SO3 - ·····HN +HSO2- zwitterionic groups, and then acid ion exchange to obtain long and short branched chain sulfonic acid groups, after washing and drying to obtain long and short branched chain perfluorosulfonic acid resin;
[0025] Method (2), when Ar is a cationic group with other positively charged groups, the intermediate product is subjected to a grafting reaction with a Q-Ar2 reagent and a Q-Ar1 reagent with a cationic group in an organic solvent to graft a long-chain -SO 3- and cationic groups; the product finally undergoes an acid ion exchange process to obtain long and short branched chain sulfonic acid groups, and after washing and drying, a long and short branched chain perfluorosulfonic acid resin is obtained.
[0026] The above reaction formula is as follows:
[0027]
[0028] Preferably, the Q-Ar1 reagent is composed of one of the cationic structures in the structure shown in Formula III and a counter ion:
[0029]
[0030] Preferably, the cationic structure in the Q-Ar1 reagent is One of them.
[0031] Preferably, when the counter ion in the Q-Ar1 reagent is Cl - Br - ,I - When alkali or acid ion exchange is carried out, the ion is exchanged for OH - , [(CF3SO2)2N] - , (H2PO3) - wait.
[0032] The Q-Ar2 reagent is a reagent with a sultone structure, and its general structural formula is shown in Formula IV, wherein m is an integer ≥ 2;
[0033]
[0034] Preferably, according to the present invention, the organic solvent in the preparation method is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, isopropanol, dichloromethane, acetone, dimethyl sulfoxide or ethyl acetate.
[0035] The ammonia reagent is aqueous ammonia or liquid ammonia. According to the preferred embodiment of the present invention, the molar ratio of PFSO2F resin to ammonia in the method is 1:5-20, preferably 1:10-15; the molar ratio of the intermediate product to the Q-Ar1 and Q-Ar2 reagents is 1:5-12, preferably 1:6-10.
[0036] Preferably, according to the present invention, the temperature of the grafting reaction in step 2 is 70-90° C., preferably 80° C.; the reaction time is 10-15 hours, preferably 12 hours.
[0037] Preferably, according to the present invention, the pre-swelling in step 1 is to swell the perfluorosulfonyl fluoride resin in an organic solvent at 45-55° C. for 50-70 minutes.
[0038] The long and short branched perfluorosulfonic acid resin prepared above can determine the ion exchange capacity and the proportion of short-chain branched perfluorosulfonic acid and long-chain branched perfluorosulfonic acid structural units by acid-base titration. According to the requirements of product performance, the ratio of long and short branches can be controlled by adjusting the reaction time, reaction temperature and raw material ratio in the preparation method, thereby adjusting the ion exchange capacity of the resin and the proportion of each functional unit.
[0039] Another object of the present invention is to provide a proton membrane containing the long and short branched perfluorosulfonic acid resin.
[0040] Preferably, the mass content percentage of the long and short branched perfluorosulfonic acid resin is 1 to 100%.
[0041] The present invention also provides the application of the long and short branched perfluorosulfonic acid resin in a fuel cell.
[0042] Technical effects of the present invention:
[0043] Compared with the prior art, the present invention has at least the following advantages:
[0044] (1) The long and short branched perfluorosulfonic acid resin and proton membrane provided by the present invention have a side chain structure combining a short branched perfluorosulfonic acid structure with a long branched perfluorosulfonic acid structure, and have high dimensional stability and high ion conductivity.
[0045] (2) The introduction of long-chain perfluorosulfonic acid structure can regulate the water absorption rate of resin and membrane and improve dimensional stability; in addition, the cationic group in the structure can effectively increase the dissociation of the terminal sulfonic acid group, improve the ionic conductivity, and resolve the contradiction between "long side chain" and "low conductivity".
[0046] (3) The sulfonic acid groups in the short-chain perfluorosulfonic acid structure can form acid-base ion pairs with the amino groups (-N-) in the long-chain perfluorosulfonic acid structure, thereby enhancing the intermolecular interaction and effectively limiting the strong water absorption of the sulfonic acid groups in the proton membrane, which can greatly enhance the mechanical properties of the membrane. In addition, the formed ion pairs can also conduct ions, resolving the contradiction between "short side chains" and "high swelling".
[0047] (4) Benefiting from the Donnan exclusion effect (positive charges repel each other), the introduction of cationic structural units into the resin and membrane structure can effectively inhibit the penetration of positively charged ions in the zwitterionic membrane, and has excellent alcohol and vanadium resistance properties.
[0048] (5) The long and short branched structural units in the perfluorosulfonic acid resin provided by the present invention have the function of regulating the crystallinity and water absorption of the polymer and improving the mechanical properties and ionic conductivity of the resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 : is the infrared test spectrum of each resin in the embodiment, wherein A is PFSO2F resin, B is intermediate product A1, C is target product A2, and D is target product A3;
[0050] Figure 2 It is a device for testing the vanadium ion permeability of membranes. DETAILED DESCRIPTION
[0051] To further help understand the technical solution of the present invention, the technical solution of the present invention is described in more detail below by providing several specific implementation examples.
[0052] The raw materials and reagents involved in the examples, unless otherwise specified, are common commercially available products; the experimental methods involved in the examples, unless otherwise specified, are conventional technical means in the art.
[0053] The wavy line of the present invention represents an alkyl chain or perfluoroalkyl chain of any length or H. The length is schematic and does not represent the actual length.
[0054] Example 1
[0055] A preparation method of a long and short branched perfluorosulfonic acid resin, wherein a grafting reaction is performed according to a preparation method to graft long and short branched perfluorosulfonic acid groups. PFSO2F resin (a'=4, b'=1; x', y', z'=1, number average molecular weight of 420,000, molar equivalent E w =869g / mol), the specific steps are as follows:
[0056] (1) A 500 mL sealed reactor was cleaned, evacuated and replaced with high-purity nitrogen three times, and then 50 g of PFSO2F resin and 150 mL of dry N,N-dimethylacetamide were added. The stirring device was turned on and slowly heated to 50°C and maintained for 60 min. The product was filtered and repeatedly washed with deionized water three times to obtain a pre-swollen resin.
[0057] (2) The reactor was cleaned and evacuated again and replaced with high-purity nitrogen three times, and then the pre-swollen resin and 200 ml of 10% ammonia solution were added, with the molar ratio of PFSO2F resin to ammonia being 1:10; the stirring device was turned on, and the mixture was slowly heated to 30°C and maintained for 100 min. The pressure in the reactor was controlled below 0.15 MPa, and part of the -SO2F group was converted into -SO2NH2 (the reaction degree was controlled by the reaction time, and then the -SO2F reaction degree was determined by titration of IEC). The product was filtered and repeatedly washed with deionized water three times, and then immersed in 15% KOH at 70°C for 24 h to complete ion exchange, and the remaining -SO2F was converted into -SO3K. The product was washed with deionized water; and finally dried at 60°C to obtain a long and short branched intermediate product, denoted as A1, with the following reaction formula:
[0058]
[0059] Figure 1 PFSO2F( Figure 1 , A) and A1( Figure 1 , B) infrared transmission spectrum was measured. It can be seen from the figure that at 1467cm -1 The infrared absorption peak attributable to the sulfonyl fluoride group (-SO2F) appeared at the position of the intermediate product A1, and the infrared absorption peak of the -SO2F group disappeared. -1 and 1548cm -1 The characteristic peaks of -SO2NH2 primary amine (-NH2 group) appeared at 1390cm -1 and 1060cm -1 SN bonds and -SO3 appear nearby - The characteristic peak (-SO3K group) of
[0060] (3) 10 g of the obtained A1 was added to 200 mL of dry N, N-dimethylacetamide, the stirring device was turned on, and the mixture was slowly heated to 80°C. After the mixture was completely dissolved, 0.025 g of allyl trimethyl ammonium chloride was added. The molar ratio of A1 to allyl trimethyl ammonium chloride (Q-Ar1 reagent) was about 1:8. After the addition was completed, -SO2NH2 was used to react with the double bond under mechanical stirring at 80°C to undergo an Aza-Michael addition reaction to graft the quaternary ammonium cationic group. After reacting for 12 hours, the mixture was cooled to room temperature, the product was filtered, and the unreacted allyl trimethyl ammonium chloride was removed by washing with deionized water for several times. The product was dried at 60°C. The product was then subjected to a ring-opening reaction with tetrafluorosulfone (Q-Ar2 reagent, m=2) to graft the SO3 -Cationic group (the reaction process is the same as that of A1 and Q-Ar1, and the reactants react in the same molar ratio), and finally washed three times with deionized water, and then soaked in 15% sulfuric acid for 20 hours to complete ion exchange, and the product was washed with deionized water; finally, it was dried at 60°C to obtain a long and short branched perfluorosulfonic acid resin, recorded as A2, and the reaction formula is as follows:
[0061]
[0062] The product A2( Figure 1 , C) Infrared transmission spectrum measurement, it can be seen that at 3304 ~ 3400cm -1 and 1548cm -1 The characteristic peak (-NH2 group) belonging to the primary amine -SO2NH2 disappears, and at 3300cm -1 The characteristic peak of -NH- appeared near 3038~3110cm -1 The characteristic peaks of -CH2 and -CH3 appeared at 1478 cm -1 There was a strong The characteristic peak at 1060cm -1 -SO3 - The above results prove that the target product A2 was successfully obtained.
[0063] After ion exchange capacity (IEC) measurement, the IEC of the obtained target product A2 is 1.05 mmol / g, the molar proportion of tetrafluoroethylene structural units in the copolymer is 49.00%, the molar proportion of short-chain branched perfluorosulfonic acid structures is 27.50%, and the molar proportion of long-chain branched perfluorosulfonic acid structural units is 23.50%.
[0064] Example 2
[0065] A long and short branched perfluorosulfonic acid resin is prepared. First, the intermediate product A1 is prepared according to the method of Example 1, except that the PFSO2F resin (E w =800g / mol) and ammonia in a molar ratio of 1:15; the reaction time is extended from 100min to 200min to prepare a long and short branched intermediate product, 1-allyl-3-methylimidazolium chloride is used as Q-Ar1 reagent, and the other components, material ratios and synthesis methods are the same as in Example 1 to obtain a long and short branched perfluorosulfonic acid resin, denoted as A3, and the reaction formula is as follows:
[0066]
[0067] The ion exchange capacity (IEC) was measured and the IEC of the obtained target product A3 was 1.20 mmol / g.
[0068] The molar proportion of tetrafluoroethylene structural units in the copolymer is 46.00%, the molar proportion of short-chain branched perfluorosulfonic acid structural units is 26.50%, and the molar proportion of long-chain branched perfluorosulfonic acid structural units is 27.50%.
[0069] Example 3
[0070] A long and short branched perfluorosulfonic acid resin is prepared. First, the intermediate product A1 is prepared by referring to the method of Example 1, except that the reaction time of PFSO2F resin (Ew=680g / mol) and NH3 is extended from 100min to 300min to prepare the long and short branched intermediate product; in addition, only tetrafluorosulfone is used as the Q-Ar2 reagent to directly react with A1 for ring-opening addition reaction to prepare the long and short branched perfluorosulfonic acid resin. The other components, material ratios and synthesis methods are the same as those of Example 1. The obtained product is recorded as A4, and the reaction formula is as follows:
[0071]
[0072] The IEC of the obtained target product A4 was determined by ion exchange capacity (IEC) to be 1.40 mmol / g.
[0073] The molar proportion of tetrafluoroethylene structural units in the copolymer is 48.00%, the molar proportion of short-chain branched perfluorosulfonic acid structural units is 25.50%, and the molar proportion of long-chain branched perfluorosulfonic acid structural units is 26.50%.
[0074] Example 4
[0075] A long and short branched perfluorosulfonic acid resin is prepared. First, the intermediate product A1 is prepared by referring to the method of Example 1, except that the reaction time of PFSO2F resin (Ew=680g / mol) and NH3 is extended from 100min to 500min to prepare the long and short branched intermediate product; in addition, only perfluorobutane sultone (m=4) is used as the Q-Ar2 reagent to directly react with A1 for ring-opening addition to prepare the long and short branched perfluorosulfonic acid resin. The other components, material ratios and synthesis methods are the same as those of Example 1. The obtained product is recorded as A5, and the reaction formula is as follows:
[0076]
[0077] After ion exchange capacity (IEC) measurement, the IEC of the obtained target product A5 is 1.42 mmol / g. The reaction formula is as follows:
[0078] The molar proportion of tetrafluoroethylene structural units in the copolymer is 45.00%, the molar proportion of short-chain branched perfluorosulfonic acid structural units is 26.50%, and the molar proportion of long-chain branched perfluorosulfonic acid structural units is 28.50%.
[0079] Example 5
[0080] Preparation of a long and short branched perfluorosulfonic acid resin, which is different from Example 1 in that PFSO2F resin (a'=4, b'=1; x', z'=1; y'=0, molar equivalent E w =680g / mol) to prepare the long and short branched intermediates; the other components, material ratios and synthesis methods are the same as those in Example 1, and the obtained product is recorded as A6, and the reaction formula is as follows:
[0081]
[0082] The ion exchange capacity (IEC) was measured and the IEC of the obtained target product A6 was 1.45 mmol / g.
[0083] The molar proportion of tetrafluoroethylene structural units in the copolymer is 46.00%, the molar proportion of short-chain branched perfluorosulfonic acid structural units is 26.50%, and the molar proportion of long-chain branched perfluorosulfonic acid structural units is 27.50%.
[0084] Example 6
[0085] Preparation of a long and short branched perfluorosulfonic acid resin, which is different from Example 1 in that PFSO2F resin (a'=4, b'=1; x', z'=1; y'=0, molar equivalent E w =680g / mol) to prepare the long and short branched intermediates; in addition, only tetrafluorosulfone was used as the Q-Ar2 reagent to directly react with A1 for ring-opening addition to prepare the long and short branched perfluorosulfonic acid resin, and the other components, material ratios and synthesis methods were the same as those in Example 1. The obtained product was recorded as A7, and the reaction formula is as follows:
[0086]
[0087] The ion exchange capacity (IEC) was measured and the IEC of the obtained target product A7 was 1.45 mmol / g.
[0088] The molar proportion of tetrafluoroethylene structural units in the copolymer is 47.50%, the molar proportion of short-chain branched perfluorosulfonic acid structural units is 26.50%, and the molar proportion of long-chain branched perfluorosulfonic acid structural units is 26.00%.
[0089] Example 7
[0090] A long and short branched perfluorosulfonic acid resin is prepared, and the target product is prepared by referring to the method of Example 4, except that the reaction time of PFSO2F resin (Ew=680g / mol) and NH3 is extended from 100min to 1000min to prepare the long and short branched intermediate product; the other components, material ratios and synthesis methods are the same as those of Example 4, and the obtained product is recorded as A8, and its structural formula is the same as A5. After ion exchange capacity (IEC) measurement, the IEC of the obtained target product A8 is 1.35mmol / g.
[0091] The molar proportion of tetrafluoroethylene structural units in the obtained copolymer is 48.50%, the molar proportion of short-chain branched perfluorosulfonic acid structural units is 21.50%, and the molar proportion of long-chain branched perfluorosulfonic acid structural units is 30.00%.
[0092] Example 8
[0093] Preparation of a long and short branched perfluorosulfonic acid resin, which is different from Example 1 in that PFSO2F resin (a'=4, b'=1; x', z'=1, y'=0, molar equivalent E w =680g / mol) to prepare the long and short branched intermediates; the difference is that the reaction time of PFSO2F resin (Ew=680g / mol) and NH3 is shortened from 100min to 50min to prepare the long and short branched intermediates; the other components, material ratios and synthesis methods are the same as those in Example 6, and the obtained product is recorded as A9, and its structural formula is the same as A7. After ion exchange capacity (IEC) measurement, the IEC of the obtained target product A9 is 1.47mmol / g
[0094] The molar proportion of tetrafluoroethylene structural units in the obtained copolymer is 48.30%, the molar proportion of short-chain branched perfluorosulfonic acid structural units is 31.00%, and the molar proportion of long-chain branched perfluorosulfonic acid structural units is 20.70%.
[0095] Example 9
[0096] Prepare the resin into a proton membrane:
[0097] A homogeneous long and short branched perfluorosulfonic acid proton membrane was prepared by a solution casting method, and the specific steps were as follows: first, resin A2, resin A3, resin A4, resin A5, resin A6, resin A7, resin A8, and resin A9 were dissolved in N, N-dimethylformamide, stirred and dispersed uniformly to prepare a 10wt% homogeneous membrane-making solution, and coated on a polytetrafluoroethylene reinforced mesh (2 layers, porosity 80%, gram weight 3.2g / m 2 ), pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded, to prepare 15 μm homogeneous proton membranes, which were denoted as M2 to M9.
[0098] Comparative Example 1
[0099] The PFSO2F resin in Example 1 was soaked in 15% KOH and 25wt% sulfuric acid solutions at 80°C for 30h to complete ion exchange, and all -SO2F groups were converted into -SO3H to obtain a short-chain branched perfluorosulfonic acid resin PFSA (the molar proportion of tetrafluoroethylene polymer structural units was 55.0%, and the molar proportion of perfluorosulfonic acid structural units was 45.0%), which was recorded as resin B1. The reaction formula is as follows:
[0100]
[0101] Comparative Example 2
[0102] The PFSO2F resin in Example 1 was reacted with ammonia to convert all -SO2F groups into -SO2NH2, and the resulting product was recorded as perfluorosulfonamide (PFSO2NH2). Then, tetrafluorosulfone was used as the Q-Ar2 reagent to directly react with PFSO2NH2 to prepare a long-chain branched perfluorosulfonic acid resin (the molar proportion of tetrafluoroethylene polymer structural units was 52.0%, and the molar proportion of perfluorosulfonic acid structural units was 48.0%). The remaining components, material ratios and synthesis methods were the same as in Example 1, recorded as resin B2, and the reaction formula was as follows:
[0103]
[0104] Comparative Example 3
[0105] The molar content of the resin in Comparative Example 1 was selected to be 50.00%, and the molar content of the resin in Comparative Example 2 was selected to be 50.00%, and a long- and short-chain mixed resin was prepared, which was recorded as resin B3.
[0106] Comparative Example 4
[0107] The perfluorosulfonic acid resins B1, B2 and B3 obtained in Comparative Examples 1, 2 and 3 were selected to prepare long-chain perfluorosulfonic acid proton exchange membranes according to the steps of Example 7, which were respectively designated as D-1, D-2 and D-3.
[0108] Test method:
[0109] Titration of ion exchange capacity (IEC): Accurately weigh a certain weight of the dry target product, and then use a 1M NaCl aqueous solution for ion exchange for 12 hours to convert the counter ions of the perfluorinated anion groups in the product into Cl - , collect the solution after ion exchange, use phenolphthalein as an indicator, and titrate with 0.1M NaOH standard solution until the solution turns pink. The ion exchange capacity (IEC) value of the target product can be calculated according to the following formula:
[0110] IEC=(V NaOH ×C NaOH ) / m
[0111] Where: V NaOH ——The volume of NaOH standard solution consumed, mL; C NaOH ——molar concentration of NaOH standard solution, mmol / mL; m——mass of dry target product, g.
[0112] The mechanical properties test of the ion membrane is carried out in accordance with GB / T20042.3-2009.
[0113] The ion membrane conductivity test was carried out in accordance with GB / T20042.3-2009 (the test conditions were room temperature and 120°C).
[0114] Thermal degradation temperature (defined as the temperature at which the polymer degrades 5%): The test was conducted using a thermogravimetric analyzer, TAQ50 produced by Perkin Elmer, USA, with a N2 atmosphere, a heating rate of 10°C / min, and a temperature range of 50-800°C. The samples were dried at 60°C for 24 hours before testing.
[0115] Water absorption and swelling degree: Soak the sample in deionized water at the test temperature (test conditions are room temperature and 80°C) for 24 hours to ensure complete swelling. Take out the sample, quickly wipe off the water on the surface of the sample, and record the sample weight (M w ) and length (L w Then the sample was dried at 80°C and the sample weight (M d ) and length (L d ), water absorption and swelling degree are calculated by the following formula:
[0116] Water absorption % = [(M w -M d ) / M d ]×100%, swelling degree %=[(L w -L d ) / L d ]×100%.
[0117] Crystallinity: The present invention uses DSC2910 produced by TA Company of the United States, and tests are carried out under nitrogen protection according to the method of GB / T19466.3-2004. The sample is first heated from room temperature to 150°C at a rate of 10°C / min, and kept at a constant temperature for 5 minutes, and then naturally cooled to room temperature. Then the temperature is scanned at a rate of 10°C / min (room temperature to 150°C), and the DSC curve is recorded.
[0118] Crystallinity X i =(ΔH f / 293)×100%
[0119] Where: ΔH f is the melting enthalpy of the sample polymer, in Jg -1 293 is the melting enthalpy of polyethylene when the crystallinity is 100%, in Jg -1 .
[0120] Vanadium ion permeability of ion membrane: Figure 2 The device shown (refer to Chinese patent CN114835842A) tests the vanadium ion permeability of the membrane. The two sides of the container are 3MH2SO4 / 1.5MVOSO4 and 3MH2SO4 / 1.5MMgSO4 respectively, and the ion membrane to be tested is in the middle. Mechanical stirring is auxiliary on both sides of the container to prevent concentration polarization. As time goes by, samples are taken from the electrode solution on the right at regular intervals to test the VOSO4 concentration, and an equal amount of stock solution is added. The VOSO4 concentration test is tested by an ultraviolet spectrophotometer (JASCO, FT-IR4100, Japan), and the vanadium ion permeability is calculated by referring to the literature (Journal of Membrane Science 525 (2017) 229-239).
[0121] The water absorption, thermal stability, IEC and crystallinity of the resins obtained in the examples and comparative examples were tested. The test results are shown in Table 1.
[0122] Table 1
[0123]
[0124]
[0125] As can be seen from the above table, compared with long-chain branched perfluorosulfonic acid resin PFSA, short-chain branched perfluorosulfonic acid resin PFSA and long-chain and short-chain branched mixed resins, the long-chain and short-chain branched perfluorosulfonic acid resin prepared by the present invention has high thermal stability and high crystallinity; in addition, since the sulfonic acid group in the short-chain branched perfluorosulfonic acid structure can form an acid-base ion pair with the amino group (-N-) in the long-chain branched perfluorosulfonic acid structure, the intermolecular interaction force is enhanced, the water absorption rate of the sulfonic acid resin is effectively limited (less than 30%), and the stability of the resin is improved.
[0126] The conductivity, swelling degree, tensile strength and vanadium ion permeability of the exchange membranes obtained in the examples and comparative examples were tested. The test results are shown in Table 2.
[0127] Table 2
[0128]
[0129] As can be seen from the above table, the long and short branched perfluorosulfonic acid proton membrane disclosed in the embodiment of the present invention has better mechanical properties, dimensional stability and lower vanadium ion permeation than the proton membrane in the prior art. In addition, by regulating the proportion of long and short branched structural units in the resin, the vanadium resistance performance of the proton membrane can be improved while maintaining the conductivity and mechanical properties of the proton membrane, which can solve the shortcomings of poor vanadium resistance and high swelling degree of the ion membrane, and is suitable for fuel cells, chlor-alkali electrolysis cells and water electrolysis hydrogen production electrolysis cells.
Claims
1. Long and short branched perfluorosulfonic acid resin, characterized in that: The resin structure includes a perfluoroethylene structural unit, a short-chain branched perfluorosulfonic acid structural unit (A) and a long-chain branched perfluorosulfonic acid structural unit (B), and the resin has a structure shown in the following formula I: Wherein ad is an integer from 0 to 30, and x is 0 or 1; y and z are integers of 0 to 3, the value of e is 50 to 10000, m is an integer ≥ 2, and Ar is a cationic group.
2. The perfluorosulfonic acid resin according to claim 1, characterized in that a+b / (a+b+c+d)=0.30~0.90; c+d / (a+b+c+d)=0.40~0.
80.
3. The perfluorosulfonic acid resin according to claim 1, characterized in that a, c are independently selected from 1 to 10; b, d are 1; x is 1; y, z are independently 0 or 1; m is an integer of 2 to 6.
4. The perfluorosulfonic acid resin according to claim 3, characterized in that The cationic group is H + or a cationic structure having one of the structures of formula II and a counter ion composition: The counter ion is Cl - , SO4 2- , HSO4 - , OH - One of them.
5. The perfluorosulfonic acid resin according to claim 1, characterized in that The molar percentages of the polymerized units in the resin are as follows: the molar percentage of tetrafluoroethylene structural units is 35-85%, the molar percentage of short-chain branched perfluorosulfonic acid structural units is 10-60%, and the molar percentage of long-chain branched perfluorosulfonic acid structural units is 5-55%.
6. The perfluorosulfonic acid resin according to claim 1, characterized in that The resin has both cation exchange capacity and anion exchange capacity, and the ion exchange capacity is 0.9 to 2.0 mmol / g, preferably 1.0 to 1.5 mmol / g.
7. The method for preparing the resin according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: After PFSO2F is pre-swollen in an organic solvent, it is reacted with an ammonia reagent to convert part of the -SO2F groups into -SO2NH2, and then the remaining -SO2F groups are converted into sulfonate -SO3M (M is K) through an alkaline ion exchange process. + , Na + ), after washing and drying, long and short branched chain intermediate products are obtained; Step 2: Follow one of the following methods: Method (1), when Ar is H + When the intermediate product is directly reacted with Q-Ar2 reagent to graft long-chain -SO3 - , forming -SO3 - ·····HN + HSO2- zwitterionic groups, and then acid ion exchange to obtain long and short branched chain sulfonic acid groups, after washing and drying to obtain long and short branched chain perfluorosulfonic acid resin; Method (2), when Ar is + When the intermediate product contains a cationic group with a positive charge other than the above, the intermediate product is subjected to a grafting reaction with a Q-Ar2 reagent and a Q-Ar1 reagent with a cationic group in an organic solvent to graft a long branched chain -SO 3- and cationic groups; the product finally undergoes an acid ion exchange process to obtain long and short branched chain sulfonic acid groups, and after washing and drying, a long and short branched chain perfluorosulfonic acid resin is obtained.
8. The preparation method according to claim 7, characterized in that: The Q-Ar1 reagent is composed of a cationic structure and a counter ion in the structure shown in Formula III. composition: The Q-Ar2 reagent is a reagent with a sultone structure, and its general structural formula is shown in Formula IV, wherein m is an integer ≥ 2; 9. The preparation method according to claim 7, characterized in that: The organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, isopropanol, dichloromethane, acetone, dimethyl sulfoxide or ethyl acetate; Preferably, the molar ratio of PFSO2F resin to ammonia is 1:5 to 20; the molar ratio of the intermediate product to Q-Ar1 and Q-Ar2 reagents is 1:5 to 12; Preferably, the temperature of the grafting reaction in step 2 is 70 to 90° C. and the reaction time is 10 to 15 hours; Preferably, the pre-swelling in step 1 is to swell the perfluorosulfonyl fluoride resin in an organic solvent at 45-55° C. for 50-70 minutes.
10. A proton membrane comprising the perfluorosulfonic acid resin according to any one of claims 1 to 6 or the perfluorosulfonic acid resin prepared by the method according to any one of claims 7 to 9.
Citation Information
Patent Citations
Preparation method of water retention type proton exchange membrane for fuel cell
CN101667648A
Method for preparing low-permeability proton exchange membrane for fuel cell
CN101692487A
Polymerization method of perfluorosulfonyl fluoride resin
CN114835842A
Single ion polymer electrolyte molecular design
CN114497727A
Fluorine-containing sulfonic acid resin and preparation method thereof
CN114773517A
Cited By
Preparation method of short branched chain perfluorosulfonic acid membrane, hydrogen production method and system
CN122685931A